Satyagraha of Common People. Issue 2 (December 2016) - Jha, Jyotsna
One often comes across women and men who are satyagrahis without being part of any movement. This is a piece on such satyagrahis: to celebrate them and to think about the ways and means in which satyagraha unfolds, and inspires. The article narrates stories of four different people who decided to follow the path of resistance – against the mainstream current – to be able to stand up to their own conviction and beliefs. The article argues that these and probably thousand of others who are practicing some or the other aspect of satyagraha in their daily lives, are also satyagrahis . It is time to celebrate the survival and flourishing of satyagrahi instincts of common people who are living and also dying in some cases – for their principles and conviction. This is their search for and insistence on truth, and indeed a tribute to Gandhi's satyagraha .